2012
DOI: 10.1038/ja.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the enniatins: a review of their isolation, biosynthesis, structure determination and biological activities

Abstract: Enniatins are cyclohexadepsipeptides isolated largely from Fusarium species of fungi, although they have been isolated from other genera, such as Verticillium and Halosarpheia. They were first described over 60 years ago, and their range of biological activities, including antiinsectan, antifungal, antibiotic, and cytotoxic, drives contemporary interest. To date, 29 enniatins have been isolated and characterized, either as a single compound or mixtures of inseparable homologs. Structurally, these depsipeptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 51 publications
2
110
1
1
Order By: Relevance
“…Based on previous studies and as part of our continued effort to quantify the chemical diversity of fungal isolates [6], herein we expand the analysis to a larger set of 207 compounds described by our group [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that represent twice the size of the dataset analyzed in 2012. In the current analysis, we employed molecular fingerprints as distinct molecular representations not analyzed in the previous study; also we emphasized the evaluation of molecular complexity that may have a significant impact in drug discovery endeavors, since this feature has been associated with target selectivity (and potential toxicity).…”
Section: Special Focus Issue -Antifungal Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies and as part of our continued effort to quantify the chemical diversity of fungal isolates [6], herein we expand the analysis to a larger set of 207 compounds described by our group [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that represent twice the size of the dataset analyzed in 2012. In the current analysis, we employed molecular fingerprints as distinct molecular representations not analyzed in the previous study; also we emphasized the evaluation of molecular complexity that may have a significant impact in drug discovery endeavors, since this feature has been associated with target selectivity (and potential toxicity).…”
Section: Special Focus Issue -Antifungal Drug Discoverymentioning
confidence: 99%
“…The largest fragments were kept, duplicates in each dataset were removed and all molecules with molecular weight (MW) over 1000 were excluded. The in-house library of fungal metabolites with 207 compounds (referred to hereafter as 'FUNGI') [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] was compared with the following five reference collections: 2249 compounds based on the Flavor and Extract Manufacturers Association of the United States GRAS list, updated to GRAS 27 (hereafter referred to as 'GRAS') [24,30]; FDA drugs obtained from DrugBank [31] containing: 76 drugs approved to treat cancer (hereafter referred to as 'FDA-ONC') and 1399 nononcological drugs (hereafter referred to as 'FDA-NONC'); 713 drugs in clinical trials reported by the Therapeutic Target Database [32] (hereafter referred to as 'CLINIC'); and 850 compounds from a commercial collection focused on epigenetic targets, available at Selleckchem (hereafter referred to as 'GENERAL') [33]. Supplementary Table 1 summarizes the number of duplicate molecules found in the initial datasets.…”
Section: General Approachmentioning
confidence: 99%
“…derived Iturin [120]; Fengycin [121,122] and Lichenysin [123] are well recognized by their pore forming abilities and membrane permeabilizing properties. Also, Pseudomonas derived lipopeptides [29,124,125] and fungal derived lipopeptides [126] have similar activities.…”
Section: Pore Forming Capacity Of Lipopeptide Surfactants and Relatedmentioning
confidence: 91%
“…Verticillium and Halosarpheia; has been suggested, since the 1960's, to be an ionophore [126]. In fact, they incorporate easily into the cell membrane as a passive channel and form cation selective pores.…”
Section: Pore Forming Capacity Of Lipopeptide Surfactants and Relatedmentioning
confidence: 99%
“…Also other important FHB associated agents such as Fusarium equiseti (Jestoi, 2008;Logrieco et al, 1998) and Fusarium sporotrichioides (Thrane et al, 2004) showed the ability to produce BEA and ENs, cyclic hexadepsipeptides with a similar biosynthetic pathway. The multifunctional enzymes that catalyze the biosynthesis of these mycotoxins are BEA or EN synthetases (Sy-Cordero et al, 2012;Xu et al, 2008). The corresponding gene is called esyn1 (Haese et al, 1993) and a PCR approach based on this gene for the molecular detection of potential enniatin-producing Fusarium species has been developed by Kulik et al (2007).…”
Section: Introductionmentioning
confidence: 99%